Assessment of anti-inflammatory effects of Micromeria barbata ethanolic extract and AKBA in AGE-induced inflammation in PBMC and THP-1 cell lines - Saad, May; Ayoub, Abeer J.; Khalil, Mahmoud I.; Nasreddine, Nadine (Edelweiss Applied Science and Technology, 2026)
This study investigated the anti-inflammatory effects of Micromeria Barbata (MB) and 3-O-acetyl-11-keto-β-boswellic acid (AKBA) in human PBMCs and THP-1 cells following stimulation with advanced glycation end products (AGEs). Cytotoxicity of MB, AKBA, and AGE-BSA was evaluated using MTT assays. Subsequently, RT-PCR was employed to quantify cytokine responses and assess how MB and AKBA modulated IL-6, TNF-α, and IL-1β expression in PBMCs and THP-1 cells. MTT assays confirmed that MB (5–40 µg/mL), AKBA (0.01–0.5 µg/mL), and AGE-BSA (10–100 µg/mL) were non-toxic under 24–48 hours exposure. AGE-BSA (10 µg/mL) significantly increased cytokine expression in PBMCs (IL-6, IL-1β, TNF-α: 115-, 11.7-, 0.7-fold) and THP-1 cells (325-, 11-, 7.3-fold). Pretreatment with MB or AKBA mitigated this inflammatory response in a dose-dependent manner. MB (40 µg/mL) reduced IL-6, IL-1β, and TNF-α to 0.2, 0.19, and 0.3-fold, whereas AKBA (0.3 µg/mL) resulted in 0.7, 0.6, and 0.46-fold. The study revealed that both MB and AKBA pretreatment reduced inflammatory responses in a dose-response manner to AGE-BSA in PBMC and THP-1 cells. This study offers new insights into treating AGE-induced complications and highlights potential in treating diabetes.